2005
DOI: 10.12968/jowc.2005.14.6.26792
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glycaemic control on apoptosis in diabetic wounds

Abstract: There is a significant increase in apoptosis in diabetic wounds with poorly controlled blood sugar and microangiopathy. This increase was greater in patients on OHAs than those on insulin, and it contributes to delayed wound healing. Morphological markers do not appear to be a reliable index of apoptosis in the diabetic wound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 4 publications
2
29
0
1
Order By: Relevance
“…Popularly, apoptosis index (AI) has been used to describe the density of apoptotic cells. [27][28][29] In this study, AI was defined as a percentage of the number of TUNELpositive tenocytes divided by the total number of tenocytes. The epitenon and endotenon areas were observed separately.…”
Section: Immunofluorescencementioning
confidence: 99%
“…Popularly, apoptosis index (AI) has been used to describe the density of apoptotic cells. [27][28][29] In this study, AI was defined as a percentage of the number of TUNELpositive tenocytes divided by the total number of tenocytes. The epitenon and endotenon areas were observed separately.…”
Section: Immunofluorescencementioning
confidence: 99%
“…As depicted for fibroblasts, high glucose exerts a toxic effect on endothelial cells (Berlanga-Acosta et al, 2013). High glucose concentrations has been shown to disturb endothelial cell cycle, increase DNA damage, and delay endothelial cells replication, as inducing excessive cell death (Busik, Mohr, & Grant, 2008;Callaghan, Ceradini, & Gurtner, 2005;Hink et al, 2001;Rai et al, 2005). In this aspect, further research is required to establish the role of uPA and uPAr in the impaired wound healing among patients with hyperglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…High glucose ambient has been shown to disturb endothelial cells cycle, disrupt tube formation, increase DNA damage, delay endothelial cells replication, and induce apoptosis [94]. In vitro models simulating "normoglycemia" and "hyperglycemia" have demonstrated that under a high glucose ambient, proliferation of dermal microvascular endothelial cells appear impaired [95] while apoptosis is enhanced [96] which may be related to the concomitant up-regulation of proinflammatory cytokines as TNF-α, death receptors TNF-R1 and Fas ligand in a variety of cultured endothelial cells [97].…”
Section: Diabetic Wound Endothelial Cellsmentioning
confidence: 99%